Simultaneous assessment of mitochondrial and vascular function using the Flow Mediated Skin Fluorescence technique - Marcinek, Andrzej; Katarzynska, Joanna; Gebicki, Jerzy (Frontiers in Physiology, 2025)
Flow Mediated Skin Fluorescence (FMSF) is a new non-invasive diagnostic method for assessing vascular circulation and/or metabolic regulation. The method measures stimulation of the circulation in response to post-occlusive reactive hyperemia (PORH). It analyzes the dynamical changes in NADH fluorescence emitted from skin tissue, providing information on mitochondrial metabolic status and intracellular oxygen delivery through the circulatory system. Assessment of the vascular state using the FMSF technique is based on three parameters: flowmotion (FM) under normoxia conditions, hypoxia sensitivity (HS), and hyperemic response (HRmax). The functioning of mitochondria can be assessed by analyzing the ischemic response (IRmax), hypoxia sensitivity (HS), and the basal level of NADH fluorescence. There is a close relationship between the functioning of mitochondria and the vascular system. Despite these interactions, mitochondrial and vascular regulatory function can be monitored separately as well as simultaneously by the FMSF technique. Uniquely, this approach delivers information on both mitochondrial and vascular function based on a single measurement.